PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Susanto, Priyatna Bagus; Subekti, Imam (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to examine the key factors that affect firm value on companies that listed on Indonesia Stock Exchange. This study examined factors such as CSR, independent comisaris, audit commitee, manajerial ownership, and institutional ownership whereas the dependent variable of this study is firm value. Sample from this study consist of all companies listed on the Indonesia Stock Exchange. The data used in this study is secondary data with sample selection using stratified sampling method. Analysis tools used in this study is logistic regression analysis with a significance level of 5%. The results of hypothesis testing showed variable independent commisaris, and manajerial ownership have significant effect on firm value. But not found that audit comitee, CSR, and institutional ownership affect firm value. Key words: firm value, corporate social responsibility, good corporate governance.